2004
DOI: 10.1021/je049948p
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Tension of Methane + Water with Surfactant near the Hydrate Formation Conditions

Abstract: Interfacial tension of methane + water with surfactant near the hydrate formation conditions were measured using the pendant-drop method at 273.2 K and 278.8 K and in the pressure range of (0.4 to 9.5) MPa. The concentrations of sodium dodecyl sulfate (SDS) were 100 ppm, 300 ppm, 500 ppm, 700 ppm, and 1000 ppm. It was found that the interfacial tension of the solutions decreases steeply with the addition of SDS. When the SDS concentration is about 500 ppm, the surfactant concentration reaches a critical micell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 9 publications
5
91
1
Order By: Relevance
“…The methane gas pressure at in situ is expected to be in the range of several MPa when a depressurization method is applied for gas hydrate production from hydrate deposits. However, the water retention curves were obtained under atmospheric pressure conditions and a temperature of 23-25 • C. When the pressure increases from 1 MPa to 10 MPa, it is reported that the interfacial tension between methane and water decreases from~73 mN/m to~64 mN/m at 298.15 K, varying by~12% [47][48][49]. To date, there is no contact angle measurement data available for the methane-water system on hydrophilic surfaces.…”
Section: Stress-and Strain-dependent Young's Modulusmentioning
confidence: 99%
“…The methane gas pressure at in situ is expected to be in the range of several MPa when a depressurization method is applied for gas hydrate production from hydrate deposits. However, the water retention curves were obtained under atmospheric pressure conditions and a temperature of 23-25 • C. When the pressure increases from 1 MPa to 10 MPa, it is reported that the interfacial tension between methane and water decreases from~73 mN/m to~64 mN/m at 298.15 K, varying by~12% [47][48][49]. To date, there is no contact angle measurement data available for the methane-water system on hydrophilic surfaces.…”
Section: Stress-and Strain-dependent Young's Modulusmentioning
confidence: 99%
“…The operating temperature was controlled by three Eurotherm temperature controllers with an uncertainty of ±0.1 K. All the pressure gauges were calibrated using a standard RUSKA dead-weight pressure gauge with an uncertainty of ±0.25%. Luo et al 14 and Sun et al 10,15 have used this device to measure the interfacial tension data of C 2 H 4 +water system with surfactant, CH 4 +water system with surfactant and CO 2 +crude oil+reservoir water system, respectively. Experimental procedures have been described in our previous papers.…”
Section: Apparatus and Experimental Proceduresmentioning
confidence: 99%
“…Experimental procedures have been described in our previous papers. 10,14,15 Thus only a brief description is given below.…”
Section: Apparatus and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the mechanism of the promoting effect of SDS, Sun et al (2004) hypothesised that, because the nucleation of hydrate is in part an interfacial phenomena, an interfacial property such as interfacial tension of gas and water may have great influence on the hydrate formation rate. It was then suggested that the surfactant reduces the gas-liquid interfacial tension so that gas-liquid mass transfer is improved.…”
Section: Surfactantsmentioning
confidence: 99%